2020
DOI: 10.3390/s20247166
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Portable Bioluminescence Imaging System Enabling Observation at Various Scales from Whole Mouse Body to Organelle

Abstract: Current smartphones equipped with high-sensitivity and high-resolution sensors in the camera can respond to the needs of low-light imaging, streaming acquisition, targets of various scales, etc. Therefore, a smartphone has great potential as an imaging device even in the scientific field and has already been introduced into biomolecular imaging using fluorescence tags. However, owing to the necessity of an excitation light source, fluorescence methods impair its mobility. Bioluminescence does not require illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The possibilities of the smartphone to image BL reactions occurring in biological targets was pushed forward by Hattori et al who employed a Samsung Galaxy S8+ to monitor Nanoluc chimeric proteins, called Nanolanterns (eNLs) in organelles and whole mouse body (Fig. 2D) [82][83]. An objective lens was also attached to the outer camera of the smartphone to image Ca 2+ dynamics within cellular organelles.…”
Section: When Citing Please Refer To the Published Versionmentioning
confidence: 99%
“…The possibilities of the smartphone to image BL reactions occurring in biological targets was pushed forward by Hattori et al who employed a Samsung Galaxy S8+ to monitor Nanoluc chimeric proteins, called Nanolanterns (eNLs) in organelles and whole mouse body (Fig. 2D) [82][83]. An objective lens was also attached to the outer camera of the smartphone to image Ca 2+ dynamics within cellular organelles.…”
Section: When Citing Please Refer To the Published Versionmentioning
confidence: 99%
“…Min et al demonstrated a field-deployable smartphone-based lateral flow assay (LFA) analyzer that provided quantitative analysis and enhanced the sensitivity of commercial LFA rapid kits [ 12 ]. Furthermore, smartphones are also widely applied in other types of optical sensing methods such as bioluminescence [ 13 , 14 ], colorimetric [ 15 , 16 ], and spectroscopic detections [ 17 , 18 ]. They are also integrated into the electrochemical sensing platforms as amperometric, potentiometric, and impedimetric biosensors [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although their performance was originally overshadowed by CCDs, due to competition in the consumer mobile electronics market and their prevalence in these devices, there has been heavy investment towards improving their performance that now makes them direct competitors with CCD sensors. CMOS sensors have broader representation in biological publications, having been used to measure chemiluminescence (Zangheri et al, 2015;Zangheri et al, 2021), and firefly (Kim et al, 2017;Michelini et al, 2019;Hattori et al, 2020) and bacterial luciferase (Ma et al, 2020) activity in animals, cultured human cells, and bacteria.…”
Section: Introductionmentioning
confidence: 99%